2019
DOI: 10.3389/fonc.2019.00872
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Basophilia May Suggest an “Accelerated Phase” in the Evolution of CALR-Positive Primary Myelofibrosis Toward Acute Myeloid Leukemia

Abstract: Basophils are white blood cells that play an important role in the human immune system. These cells physiologically increase in number in immune response to certain allergies, chronic inflammation, and parasitic infections. Basophils are also a significant indicator for the presence of certain malignancies such as chronic myeloproliferative neoplasms and acute myeloid leukemia. In the current manuscript we present a statistically significant correlation between persistent basophilia in primary myelofibrosis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The presence of this gene is included in the current diagnostic criteria of Ph (−) MPN ( 24 ). The AML patients converted from MPN had more CALR mutation rate frequency ( 25 ). Moreover, there are reports that the expression of CALR is remarkably higher than other hematologic malignancies, such as ambiguous lineage, ALL, MPN, MDS/MPN ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this gene is included in the current diagnostic criteria of Ph (−) MPN ( 24 ). The AML patients converted from MPN had more CALR mutation rate frequency ( 25 ). Moreover, there are reports that the expression of CALR is remarkably higher than other hematologic malignancies, such as ambiguous lineage, ALL, MPN, MDS/MPN ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dobrowolski and colleagues [59] demonstrated that correlation of leukemic transformation risk and persistent basophilia in PMF in the fibrotic stage was statistically significant. Other groups showed that monocytosis was a strong adverse indicator of progression to the accelerated phase and inferior survival in patients with PMF [60-62].…”
Section: Retrospective Studies Risk Factors and Prognostication In Mpn-apmentioning
confidence: 99%
“…Monocytosis has also been reported as a strong indicator of AP and inferior survival in patients with PMF [ 84 , 85 ]: in a large case series, the presence of an absolute monocytosis (≥1 × 10 9 /L and >3 × 10 9 /L) increased the hazard risk of leukemic transformation by 2- and 4-fold, respectively [ 85 ]. Dobrowolski and colleagues reported persistent basophilia in advanced-stage PMF patients as a risk for leukaemic transformation [ 86 ].…”
Section: Leukemic Progressionmentioning
confidence: 99%